2018
DOI: 10.1111/os.12393
|View full text |Cite
|
Sign up to set email alerts
|

Is Ambulatory Status a Prognostic Factor of Survival in Patients with Spinal Metastases? An Exploratory Meta‐analysis

Abstract: This study was conducted to identify the influence of ambulatory status prior to treatment on survival of patients with spinal metastases. Two investigators independently retrieved relevant electronic literature in PubMed, Embase, and Cochrane Library databases, to identify eligible studies. Effect estimates for hazard risk (HR) were extracted and synthesized through fixed-effects or random-effects models as appropriate. A total of 17 eligible studies were identified, with an accumulated number of 3962 partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Preoperative ambulatory status has been identified as a significant prognostic factor in patients with spinal metastases in a meta–analysis, with the suggestion that this status should be considered when choosing the treatment modality [ 30 ]. In the current study, the preoperative Frankel grade differed significantly between patients with and without survival for >6 months in univariate analysis; however, no significant difference was observed in the survival period between nonambulatory (Frankel A–C) and ambulatory (Frankel D and E) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative ambulatory status has been identified as a significant prognostic factor in patients with spinal metastases in a meta–analysis, with the suggestion that this status should be considered when choosing the treatment modality [ 30 ]. In the current study, the preoperative Frankel grade differed significantly between patients with and without survival for >6 months in univariate analysis; however, no significant difference was observed in the survival period between nonambulatory (Frankel A–C) and ambulatory (Frankel D and E) cases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the survival rate was not only affected by the choice of treatment but also other factors were included, so the highly selection of spinal metastatic patients who seemed to have better prognosis and outcome after the treatment was required. One of the significant prognostic factors in spinal metastasis patients was reported to be ambulatory status [ 21 ]. Schoenfeld et al [ 9 ] reported a QALY of 0.800 among patients who received nonoperative treatment, and a QALY of 0.823 in patients with independent ambulatory status at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, decompressive surgery is not indicated for patients with a severely limited lifespan for only a few weeks, while supportive care or radiotherapy is appropriate. Therefore, life expectancy drives treatment regimens for spinal metastasis.…”
Section: Introductionmentioning
confidence: 99%